Navigating Regulations: Adaptation Strategies of Airbnb Hosts in Barcelona - Pouleth Aquelina, Mendivil Perez (Universidad ESAN, 2025)
This study explores how Airbnb hosts in Barcelona have adapted to increasingly strict local regulations on shortterm rentals. Using a mixed-methods approach, the research combines qualitative interviews with Airbnb hosts and professionals with quantitative data from InsideAirbnb. The objective was to assess how regulatory changes have influenced hosting strategies, economic outcomes, and market visibility. The qualitative findings reveal two major trends: a shift toward partial legality (e.g., renting rooms instead of entire units) and the development of informal networks outside Airbnb, such as through social media or private referrals. These adaptations reflect both compliance efforts and circumvention strategies. The quantitative analysis supports these patterns, showing an increase in illegal listings post-2020, and a notable difference in pricing and availability depending on licensing status. Licensed listings command higher average prices, but are less common, suggesting a tradeoff between legality and profitability. The results suggest that regulation does not necessarily reduce rental activity, it reshapes it. Hosts adapt not only by adjusting rental models but also by shifting to semi-visible or invisible platforms. This evolution challenges the effectiveness of regulatory frameworks and highlights the need for more context-sensitive and adaptive policy tools.
Keywords: Adaptación al cambio; Economía colaborativa; Alquiler; Alquiler de vivienda; https://purl.org/pe-repo/ocde/ford#5.02.04